Effect of Hydrolysed and Unhydrolysed Whey Protein Bound Iron Supplement on Wistar Rats - Smitha J Lukose; Divya M.P.; Dipu M.T.; Bibu John Kariyil; A.K.Beena; S.N. Rajakumar; Deepa Ananth; P. Sudheer Babu (The Indian Veterinary Journal, 2024)
The study evaluated the body stores of iron in anaemic wistar rats after feeding with iron-fortified, whey protein concentrate (WPC)-based supplements. Both hydrolysed and unhydrolysed WPC were used for preparing WPC-iron complexes. Thirty-six male Wistar rats of three weeks of age, divided into six groups, were fed on standard diet, iron-deficient diet, diet with added mineral form of iron, diet with iron as unhydrolysed protein-iron complex ,diet with hydrolysed protein-iron complex , and diet with hydrolysed protein-iron complex with added Vitamin C respectively. Wistar rats that were made anaemic initially by feeding iron-deficient diet were fed the experimental diets with iron supplements later as a part of study. The study indicated that all the three whey based supplements had better iron regeneration capacity than the positive control. The maximum effect was indicated in hydrolysed protein iron complex with Hb of 14.57 g/dL and 48% increase on replenishing. The average Hb of control group was 13.1 g/dL. Vitamin C was not found to have any additional effect on iron bioavailability than that for hydrolysed protein –iron complex.